1983
DOI: 10.1037/0022-3514.44.6.1284
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, information, interpersonal impacts, and adjustment to a stressful health care situation.

Abstract: Forty patients scheduled for dental extraction surgery were given either specific or general preparatory information, and this information was presented in either a personalized or relatively impersonal fashion using nonverbal cues. Changes in state anxiety over the course of the experiment were accounted for by individual differences in the Dental Anxiety Scale. The most important determinant of adjustment during surgery was the congruence between specificity of information received and individual differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 29 publications
6
66
1
2
Order By: Relevance
“…Our fi nding with regard to psychological impact of diagnostic testing as compared with therapeutic procedures concurs with prior evidence in radiology and other domains. Mueller et al ( 32 ) observed that diagnostic testing (ie, computed tomography-guided chest or abdominal biopsy) resulted in more anxiety than did more complicated treatments (ie, procedures ( 6,10 ). Patients with negative affect also tend to have longer procedural times than do others, and they request and receive more medication, which may result in an increased likelihood of adverse events ( 6 ).…”
Section: Health Policy and Practice: Distress In The Radiology Waitinmentioning
confidence: 99%
See 1 more Smart Citation
“…Our fi nding with regard to psychological impact of diagnostic testing as compared with therapeutic procedures concurs with prior evidence in radiology and other domains. Mueller et al ( 32 ) observed that diagnostic testing (ie, computed tomography-guided chest or abdominal biopsy) resulted in more anxiety than did more complicated treatments (ie, procedures ( 6,10 ). Patients with negative affect also tend to have longer procedural times than do others, and they request and receive more medication, which may result in an increased likelihood of adverse events ( 6 ).…”
Section: Health Policy and Practice: Distress In The Radiology Waitinmentioning
confidence: 99%
“…Diagnostic tests, however, in herently harbor uncertainty, which can be a potent stressor and has been linked to poor coping with health-related issues, as well as poor adaptation and recovery ( 9 ). Untreated distress not only has its human toll for the patient, but also considerably taxes departmental resources in terms of appointment cancellations, patients' lack of cooperation, extended room times, increased medication use, prolonged recovery, and inability to complete imaging procedures well or at all, with adverse impact on both image quality and reimbursement ( 6,(10)(11)(12)(13)(14).…”
Section: Participantsmentioning
confidence: 99%
“…Esta informação pode ter vários formatos de apresentação; folhetos, fitas cassete, vídeos ou conversação. A efetividade desta técnica depende do estilo de afrontamento ou enfrentamento do paciente ("vigilante" ou "evitador"), beneficiando-se mais os pacientes vigilantes, e chegando inclusive a ser prejudicial para os evitadores (Auerbach, Martinelli & Mercuri, 1983;Miller & Mangan, 1983;Greene, 1989).…”
Section: Hipnoseunclassified
“…Studies show that most patients due to undergo surgical procedures demonstrate moderate to high levels of anxiety (Anderson & Masur, 1983;Auerbach, Martelli & Mercuri, 1983;Domar e t al., 1987;Ramsay, 1972). As Totman (1987) points out, this is hardly surprising since the patient, who has probably been on a long waiting list, is formally admitted to a strange and rather threatening environment, is administered to in a variety of technologically sophisticated and alarming ways and is systematically rendered unconscious having signed a form apparently exempting those giving the treatment from blame should anything go wrong.…”
mentioning
confidence: 99%